Hubungan antara kesepian dan keterlibatan ayah pada remaja - Sutanto, Sandra Handayani; Suwartono, Christiany (Konsorsium Psikologi Ilmiah Nusantara, 2019)
Apart from the noise and spark of the city, loneliness is often still engulfing teenagers. Previous research found that relationships with peers and parents were predictors of loneliness experienced by adolescents. However, no study has specifically examined parental involvement, especially father involvement. This study also aims to reveal the participation of fathers in parenting with loneliness in adolescents. This research is a quantitative study using a measurement tool adaptation from the UCLA Loneliness Scale and Father Involvement Scale. The sample size of this study was 189 adolescents by convenience sampling technique. The results showed that most teenagers felt lonely but were not related to father involvement in their lives. Discussion of the study tried to elaborate on the factors of location for data collection, developmental stages, and habits of adolescents. The results of the additional analysis showed that female adolescents tended to experience loneliness compared to male adolescents. Suggestions for research are given to get a more comprehensive picture of the phenomenon of loneliness in adolescents. Also, practical advice is also given to reduce loneliness in young women.